2019
DOI: 10.1073/pnas.1904071116
|View full text |Cite
|
Sign up to set email alerts
|

A major role for noncoding regulatory mutations in the evolution of enzyme activity

Abstract: The quantitative evolution of protein activity is a common phenomenon, yet we know little about any general mechanistic tendencies that underlie it. For example, an increase (or decrease) in enzyme activity may evolve from changes in protein sequence that alter specific activity, or from changes in gene expression that alter the amount of protein produced. The latter in turn could arise via mutations that affect gene transcription, posttranscriptional processes, or copy number. Here, to determine the types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Linked nucleotide polymorphisms in the Fast allele therefore increase ethanol tolerance only in adults, in contrast to amino acid polymorphism T192, which increases ethanol tolerance only in larvae. The transgenic Fast allele we used has been shown to increase expression compared to the Slow allele, and the alcohol dehydrogenase activity in lysate from these flies is similar to that of natural Fast and Slow strains, respectively (68). Both coding and regulatory aspects of the Fast allele therefore contribute to increased ethanol resistance, at different life stages.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Linked nucleotide polymorphisms in the Fast allele therefore increase ethanol tolerance only in adults, in contrast to amino acid polymorphism T192, which increases ethanol tolerance only in larvae. The transgenic Fast allele we used has been shown to increase expression compared to the Slow allele, and the alcohol dehydrogenase activity in lysate from these flies is similar to that of natural Fast and Slow strains, respectively (68). Both coding and regulatory aspects of the Fast allele therefore contribute to increased ethanol resistance, at different life stages.…”
Section: Resultsmentioning
confidence: 98%
“…We tested this possibility by engineering transgenic flies containing a naturally occurring Fast Adh allele, which corresponds precisely in its boundaries to that of our Slow and Slow+T192 alleles. The Fast allele construct comprises the entire coding sequence, all introns, and flanking regions that include all previously characterized cis -regulatory regions known to affect Adh expression, including the Δ1 indel polymorphism that cosegregates with T192 (49, 50, 68). We compared ethanol resistance of these transgenic Fast-allele flies at varying temperature to those carrying the Slow and Slow+T192 alleles described above.…”
Section: Resultsmentioning
confidence: 99%
“…We would like to draw attention to recent work from this laboratory which reported two pertinent observations from the analysis of the evolution of increased alcohol dehydrogenase (Adh) gene activity in certain Drosophila species. Specifically, it was found that the expression of tandem gene duplicates is often greater than twofold that of single genes (49) and that a tandem gene duplication produced the single largest quantitative effect on Adh protein activity of a variety of individual mutations among several Drosophila species (49). The relevant implication of these studies is that selection for greater gene expression is sufficient to favor the retention of a gene duplicate without any prior or subsequent innovative mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative is that protein dysfunction associated with CG-insensitivity substitutions is in some cases compensated by the up-regulation of ATPα1 expression (see for e.g. Loehlin et al, 2019), which may be an important driver of recurrent ATPα1 duplication and is observed across multiple CG-adapted insects (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%